Implementasi Pelaksanaan Program Kartu Prakerja di Kota Binjai - Ikhwa Sasmitha (Yayasan Literasi Sains Indonesia, 2023)
Poverty is a global problem that continues to find a way out. One of the factors triggering the high poverty rate is that there are still many people who experience unemployment at work. This is exacerbated by the Covid-19 pandemic disaster, one of which has an impact on the economic sector and has resulted in high levels of layoffs in almost all regions of Indonesia. One of the government's efforts in overcoming this problem is by issuing the Kartu Prakerja program. However, in reality there are still many obstacles in the implementation of the Kartu Prakerja program. This study aims to determine how the implementation of the Kartu Prakerja program in Binjai City. The data collection techniques used were observation and interviews. Based on the research that has been conducted, the results of this study indicate that the implementation of the Kartu Prakerja program in Binjai City has been carried out quite well. The obstacles experienced by the community include internet network problems, errors on the Kartu Prakerja website, people who are less digitally proficient, and video material that seems monotonous and boring.